Breed and management comparisons and genetic parameters for carcass traits - Andries, K.M.; Schalles, R.R.; Franke, D.E.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Carcass data from 5 years of a long-term, rotational , crossbreeding project were used to calculate heritabilities, genetic and phenotypic correlations , and management effects and to compare breeds for marbling, ribeye area, and hot carcass weight. Angus, Brahman, Charolais, Hereford, Polled Hereford, Gelbvieh, and Simmental breeds were involved. Sixty percent of the steer calves were fed as calves and 40% as yearlings. Heritabilities were .40 for marbling, .46 for ribeye area, and .51 for carcass weight. Genetic and phenotypic correlations were high between carcass weight and ribeye area but low between marbling and the other traits. Steers fed as calves had more marbling and lighter carcasses than steers fed as yearlings. Higher percentages of Gelbvieh or Brahman breeding resulted in lower (P<.05) marbling . Increased percentage of Charolais and Simmental breeding increased (P<.05) ribeye area and tended to increase carcass weight without reducing marbling.
Keywords: Beef; Postweaning management; Genetic parameters; Carcass traits; Breeds; Beef cattle